The emerging roles of ferroptosis in cells of the central nervous system - Li, Yuyao; Xiao, Dongqiong; Wang, Xiaodong (Frontiers in Neuroscience, 2022)
Ferroptosis is morphologically characterized by shrunken mitochondria and biochemically characterized by iron overload, lipid peroxidation and lipid reactive oxygen species (ROS) accumulation; these phenomena are suppressed by iron chelation, genetic inhibition of cellular iron uptake, and intervention on other pathways such as lipid metabolism. The induction of ferroptosis may be related to pathological cellular conditions in the central nervous system (CNS); thus, ferroptosis may cause disability via CNS damage. Here, we review the role of ferroptosis in the main cells of the CNS, including glial cells, neurons, and pericytes; in various diseases of the CNS; and in the interaction of glia and neurons in CNS diseases. Some small molecules and traditional Chinese drugs which inhibit ferroptosis in cells of the CNS are shown as potential therapeutic strategies for neurological diseases.